Rare case report of huge inflammatory pseudotumor of the mandible. Issue 3 (May 2016) - Sato, Toshihisa; Suenaga, Hideyuki; Sugiyama, Madoka; Hoshi, Kazuto; Takato, Tsuyoshi
Abstract: Inflammatory pseudotumor (IPT) is a rare benign non-neoplastic lesion. The etiology and the pathogenesis are yet to be understood. Aggressive progression, together with confusing radiological signs, is often mistaken as malignant. We report here a rare case of aggressive IPT in the mandible. In this case a neoplastic lesion or a systemic disease was initially suspected after incisional biopsy. Initial diagnostic treatment with steroids showed a little improvement, which indicated a reactive lesion, IPT. After steroid administration, the residual lesion was resected. Eighteen months postoperative follow-up showed neither recurrence nor progression.